Resistência de união à cerâmica ZLS em diferentes tempos de condicionamento ácido e protocolos de cimentação, após envelhecimento - Thiesen, Kevelin Poliana Palma Rigo (2017)
Objective. To assess the influence of two etching times, three different cementation protocols, and thermal cycling aging on the bond strength between a zirconia-reinforced lithium silicate ceramic and an adhesive resin cement. Method. Ceramic blocks were sectioned in 120 slices with thickness of 1.4 mm and randomly distributed in 12 groups (n = 10). After 5% hydrofluoric acid etching for 20 or 30 s, the adhesive area was delimited with a duct tape and silanized. Resin cement cylinders were cemented from a Teflon mold, following three different combinations: Silane (Si) + Cement (Ci), Si + Adhesive (Ad) + Ci, and Ad + Ci. After photopolymerization through the ceramic, the samples were stored in deionized water at 37°C for 7 days, and then subjected to the microshear bond strength test. Results. After the normality test, data were analyzed by ANOVA, showing statistical difference (p<0.01) for the three factors isolated, the double interaction between the factors of etching time and thermal cycling (p<0.05), and the triple interaction of the factors (p<0.05). Significance. The 5% hydrofluoric acid etching for 30 s and the use of the cementation protocol Scotchbond™ Universal Adhesive + RelyX™ Ultimate Cement presented higher adhesive bond strength after thermal aging, for Suprinity™ ceramics.